Service quality and customer satisfaction : A study at Majlis Bandaraya Melaka Bersejarah / Mohammad Yusuf Yahya and Muhammad Nadzim Mohd Johan - Yahya, Mohammad Yusuf; Mohd Johan, Muhammad Nadzim (Faculty of Administrative Science and Policy Studies, 2013)
Our research project paper title is ‘Service Quality and Customer Satisfaction: A Study at Majlis Bandaraya Melaka Bersejarah Area’. We want to study about the customer satisfaction towards Majlis Bandaraya Melaka Bersejarah (MBMB) area because the issue raising which the customer is not satisfied with the service that MBMB delivered to them. Our research objectives is to identify any significance relationship between service quality and customer satisfaction towards local government basic services, to recognize the most influential factor affecting customer satisfaction towards local government basic services, and to recognize the least influential factor affecting customer satisfaction towards local government basic services. Our research method is from the citizen from Bandar Melaka, Padang Temu, and Padang Semabok; stratified sampling technique of 387 respondents will be selected and surveyed to determine any relationship between the service quality attributes with the level of customer satisfaction. The questionnaire will be distributed to the respondent to get information about their level of satisfaction toward MBMB services delivered. Other than that in this research, data will be analyzed using the statistical correlations between measured variables.